2005
DOI: 10.1658/1402-2001(2005)008[0103:ssbipp]2.0.co;2
|View full text |Cite
|
Sign up to set email alerts
|

Soil seed banks in Pinus ponderosa forests in Arizona: Clues to site history and restoration potential

Abstract: Question: How does the relationship between the viable soil seed bank species composition and the above-ground vegetation in northern Arizona Pinus ponderosa forests differ under varying historical land use disturbances (low, intermediate, high)? Is above-ground vegetation correlated to the viable soil seed bank immediately following soil disturbance from restoration thinning treatments? Location: Northern Arizona, USA. Methods: Soil seed bank samples were taken along replicated transects and collected with a … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
22
0

Year Published

2006
2006
2015
2015

Publication Types

Select...
8
1

Relationship

4
5

Authors

Journals

citations
Cited by 26 publications
(26 citation statements)
references
References 52 publications
4
22
0
Order By: Relevance
“…Our results showing forbs as the dominant seed bankers agrees with other recent seed bank studies [37,38] yet the forbs appear to be maintained in the seed bank and do not reach the aboveground as found in other disturbed sites [37]. Forbs seemd to be driving the difference in overall seed densities among forest types (Figure 2).…”
Section: Seed Bankssupporting
confidence: 92%
“…Our results showing forbs as the dominant seed bankers agrees with other recent seed bank studies [37,38] yet the forbs appear to be maintained in the seed bank and do not reach the aboveground as found in other disturbed sites [37]. Forbs seemd to be driving the difference in overall seed densities among forest types (Figure 2).…”
Section: Seed Bankssupporting
confidence: 92%
“…On the other hand, Scleria sp., the most important species in the standing vegetation had a frequence of only 13% in the seed bank. This lack of correspondence has been found numerous times (Korb et al 2005, Sakai et al 2005, Hopfensperger 2007, Lang & Halpern 2007, Zobel et al 2007, Bossuyt & Honnay 2008 and has been attributed to biological differences among species (seed viabilidad and/or likelihood to be predated) or to methodology (germination technique, time of sampling, number or volume of soil samples) which may limit quantification of the soil seed bank (Brown 1992, Malo 2000, Csontos 2007). …”
Section: Discussionmentioning
confidence: 99%
“…Seed bank composition was determined with the seedling emergence method (Korb et al 2005). in January 2008, 15 sampling points were selected at random along a transect in a representative area of the plantation.…”
Section: Methodsmentioning
confidence: 99%
“…Knowledge of these seed bank characteristics could be used to predict which exotic species could become management concerns or for deciding whether to seed native species based on their abundance in seed banks (Glass 1989). Although on-or off-site seed dispersal from existing vegetation is also important (Wienk and others 2004), several studies have found partial correlations between seed bank composition and species colonizing sites after disturbance (Korb andothers 2005, Springer andHastings 2004).…”
Section: Introductionmentioning
confidence: 99%